Methodical Training Of Students Based On Adequate Models Through International Experiences (Eurasian Scientific Herald, 2026)
This article explores the theoretical and methodological foundations of employing adequate pedagogical models as a strategic mechanism for enhancing methodological training within modern educational systems. It analyzes the epistemological, axiological, and aesthetic functions of pedagogical modeling and elucidates various model types grounded in cognitive, constructivist, and competency-based approaches. Drawing on international experience, the study examines approaches that integrate case studies, project-based methodological frameworks, simulated environments, and digital technologies to foster students’ methodological competencies. Furthermore, the article highlights innovative teaching strategies such as the use of STEM educational technologies for adequate modeling processes, the practical outcomes of applied activities, and the essence of creative approaches, exemplified through international best practices. It also discusses strategies for developing complex methodological competencies in students, emphasizing the significance of modeling in teaching methods and instructional design.